2012
DOI: 10.1111/j.1399-3046.2012.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to hepatitis A and B vaccination after pediatric heart transplant

Abstract: The determination of optimal immunization protocols for immunocompromised patients is important given limited data, the potential for decreased vaccine response, and the increased threat of infection. This retrospective study assessed the response to HA and/or HB vaccination in a cohort of 13 PHTx recipients. Descriptive statistics were applied to the data, and univariate analysis was utilized to identify possible factors associated with vaccine response. HA vaccination occurred in 12 (92%) patients of whom th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A small study of 13 pediatric HT recipients reported immunity following HBV vaccination was achieved in 50% of patients; however, 30% of the included patients had only received a single HBV vaccine. 11 For patients in our study undergoing HT evaluation, seroprotection was found in 36/73 (49.3%) patients that had completed a primary HBV vaccine series.…”
Section: Discussionmentioning
confidence: 78%
“…A small study of 13 pediatric HT recipients reported immunity following HBV vaccination was achieved in 50% of patients; however, 30% of the included patients had only received a single HBV vaccine. 11 For patients in our study undergoing HT evaluation, seroprotection was found in 36/73 (49.3%) patients that had completed a primary HBV vaccine series.…”
Section: Discussionmentioning
confidence: 78%